THE EFFECT OF JOB STRESS, JOB CRAFTING, AND PERSONALITY ON THE BURNOUT OF GENERATION Z TEACHERS IN SURABAYA : PENGARUH JOB STRESS, JOB CRAFTING, DAN PERSONALITY TERHADAP BURNOUT GURU GENERASI Z DI SURABAYA - Roky Ade Boby Panduwal (SOSIOEDUKASI, 2025)
This study aims to examine the influence of job stress, job crafting and personality on burnout of Generation Z teachers in Surabaya both partially and simultaneously. This study combines job stress, job crafting, and personality in one analytical model, especially in the context of Generation Z teachers. In addition, this study found that personality is not always the main factor in reducing Generation Z burnout, which is different from several previous studies. The research method used was quantitative research involving 166 respondents of Generation Z teachers in Surabaya. The data analysis technique used multiple regression. The results found that job stress has a positive and significant effect on burnout (t-value 10.930 > t-table 1.654), while job crafting has a negative and significant effect (t-value -3.204 > t-table 1.654). Personality has no positive and insignificant effect on burnout (t-value -0.405 < t-table 1.654). Simultaneously, these three variables contribute to burnout in Generation Z teachers (F-value 76.542 > F-table 2.696). Thus, it is necessary to design strategies that focus on managing work stress, improving job crafting, and developing work adaptation programs to reduce burnout and increase the work effectiveness of Generation Z teachers.